The Influence of Maqasid Sharia on the Financial Performance of Sharia Financial Institutions - Agus Zainul Arifin; Daiki Nishida; Ren Suzuki (Journal Markcount Finance, 2025)
Maqasid Sharia, which refers to the objectives of Islamic law, plays a central role in ensuring that Sharia financial institutions operate in alignment with Islamic principles. These objectives include preserving faith, life, intellect, progeny, and wealth. While Sharia compliance is a cornerstone of Islamic finance, the extent to which Maqasid Sharia influences the financial performance of Sharia financial institutions remains underexplored. Understanding this relationship is critical for enhancing the sustainability and competitiveness of Islamic financial institutions. This study aims to examine the influence of Maqasid Sharia on the financial performance of Sharia financial institutions, providing insights into how adherence to Islamic principles can drive financial success. A quantitative research design was employed, utilizing data from 50 Sharia financial institutions in Indonesia. Multiple regression analysis was used to analyze the relationship between Maqasid Sharia compliance and financial performance indicators, such as return on assets (ROA) and return on equity (ROE). The findings reveal that higher levels of Maqasid Sharia compliance significantly improve financial performance, with institutions demonstrating strong adherence to Islamic principles reporting higher ROA and ROE. The preservation of wealth and faith emerged as the most influential dimensions of Maqasid Sharia in driving financial success. This study highlights the importance of Maqasid Sharia in enhancing the financial performance of Sharia financial institutions. The results suggest that institutions should prioritize adherence to Islamic principles to achieve sustainable growth and maintain competitiveness in the financial sector.